Physiological Aspects of Crop Productivity at Leh - Learning’s from Hot Arid Region - Burman, Uday (Annals of Arid Zone, 2016)
Scientific laboratories and agricultural research stations in cold arid region of our country especially around Leh are still in infancy. Additionally, there are meagre reports on the understanding of different interventions that may have some potential to realize high agricultural yields in cold region. Therefore, initially we need to rely on results from hot arid regions. However, in order to enhance the probability of success, commonality between the two regions with emphasis on crop response at physiological plane, need to be thoroughly understood. This should be the basis of suggesting interventions that may be adopted as such or after fine tuning keeping in view the agricultural policy of the region and in consultation with the local farmers. Crop plants in the Indian cold arid region experiences both low temperature and water stress. Many agro-techniques related to genotype and fertility management along with use of growth regulators have been successfully adopted in hot arid region. The present article discusses some of these that may have relevance in cold arid region too. However, it is imperative to mention here that before suggesting blanket recommendations it shall be appropriate to arrive at a consensus decision after active participation of local farmers, agricultural scientists and policy makers so as to develop a holistic approach for the complete development of agriculture at Leh. Key words: Arid, genotypes, fertility, management, plant physiology, low temperature, water stress.